2020
DOI: 10.1371/journal.pone.0240117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathophysiologic aspects of ECMO-associated hemorrhagic complications

Abstract: Extracorporeal membrane oxygenation (ECMO) is increasingly used to treat severe cases of acute respiratory or cardiac failure. Hemorrhagic complications represent one of the most common complications during ECMO, and can be life threatening. The purpose of this study was to elucidate pathophysiological mechanisms of ECMO-associated hemorrhagic complications and their impact on standard and viscoelastic coagulation tests. The study cohort included 27 patients treated with VV-ECMO or VA-ECMO. Hemostasis was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Popugaev et al identified the highest number of bleeding events to occur on the second or third day of treatment. 28 Hence median duration of mechanical circulatory support was 1.0 h in HRPCI-and 63.0 h in CS-patients, this suffices as an explanation for differences in transfusion in our study. Anemia in patients with acute coronary syndrome or undergoing PCI is associated with adverse outcomes.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Popugaev et al identified the highest number of bleeding events to occur on the second or third day of treatment. 28 Hence median duration of mechanical circulatory support was 1.0 h in HRPCI-and 63.0 h in CS-patients, this suffices as an explanation for differences in transfusion in our study. Anemia in patients with acute coronary syndrome or undergoing PCI is associated with adverse outcomes.…”
Section: Discussionsupporting
confidence: 56%
“…14.7% of the patients in the HRPCI and 23.1% in the CS group received more than two units of RBC during the study‐period. Popugaev et al identified the highest number of bleeding events to occur on the second or third day of treatment 28 . Hence median duration of mechanical circulatory support was 1.0 h in HRPCI‐ and 63.0 h in CS‐patients, this suffices as an explanation for differences in transfusion in our study.…”
Section: Discussionsupporting
confidence: 48%
“…[7][8][9] Bleeding represents the most frequently reported adverse event during ECLS. 10 The pathophysiology of bleeding while on ECLS is complex, although not completely understood, 11 is likely multifactorial, depending on the exposure to artificial surfaces and anticoagulation. Underlying patients' primary diagnoses and/or comorbidities, such as vasculitis or trauma, may contribute to an increased risk of bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding complications remain frequent with high morbidity and mortality 11,15–20 . The reported incidence of bleeding complications ranges between 24% and 56% 18,21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation